Performance of NiO doped on alkaline sludge from waste photovoltaic industries for catalytic dry reforming of methane - Shamsuddin, Mohd Razali; Teo, Siow Hwa; Tengku Azmi, Tengku Sharifah Marliza; Lahuri, Azizul Hakim; Yun Hin, Taufiq-Yap (Springer, 2024)
Alkali sludge (AS) is waste abundantly generated from solar photovoltaic (PV) solar cell industries. Since this potential basic material is still underutilized, a combination with NiO catalyst might greatly influence coke resentence, especially in high-temperature thermochemical reactions (Arora and Prasad, RSC Adv. 6:108,668–108688, 2016). This paper investigated alkaline sludge containing 3CaO-2SiO2 doped with well-known NiO to enhance the dry reforming of methane (DRM) reaction. The wet-impregnation method was used to prepare the xNiO/AS (x = 5–15%) catalysts. Subsequently, all catalysts were tested by using X-ray diffraction (XRD), nitrogen adsorption/desorption (BET), temperature-programmed reduction of hydrogen (H2-TPR), temperature-programmed desorption of carbon dioxide (TPD-CO2), field emission scanning electron microscopy (FESEM-EDX), and X-ray photoelectron spectroscopy (XPS). The spent catalysts were analyzed by thermogravimetric analysis (TGA/DTG), transmission electron microscopy (TEM), and temperature-programmed oxidation (TPO). The catalytic performance of xNiO/AS catalysts was investigated in a fixed bed reactor connected with gas chromatography thermal conductivity detector (GC-TCD) at a CH4:CO2 flow rate of 30 mL−1 during a 10-h reaction by following (Shamsuddin et al., Int. J. Energy Res. 45:15,463–15,480, 2021d). For optimization parameters, the effects of NiO concentration (5, 10, and 15%), reaction temperature (700, 750, 800, 850, and 900 °C), catalyst loading (0.1, 0.2, 0.3, 0.4, and 0.5 g), and gas hourly space velocity (GHSV) range from 3000, 6000, 9000, 12,000, and 15,000 h−1 were evaluated. The results showed that physical characteristics such as BET surface area and porosity do not significantly impact NiO percentages of dispersion, whereas chemical characteristics like reducibility are crucial for the catalysts’ efficient catalytic activity. Due to the active sites on the catalyst surface being more accessible, increased NiO dispersion resulted in higher reactant conversion. The catalytic performance on various parameters that showed 15%NiO/AS exhibited high reactant conversion up to 98% and 40–60% product selectivity in 700 °C, 0.2 g catalyst loading, and 12,000 h−1 GHSV. According to spent catalyst analyses, the catalyst was stable even after the DRM reaction. Meanwhile, increased reducibility resulted in more and better active site formation on the catalyst. Synergetic effect of efficient NiO as active metal and medium basic sites from AS enhanced DRM catalytic activity and stability with low coke formation. © The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature 2024.